2022
DOI: 10.1002/marc.202100720
|View full text |Cite
|
Sign up to set email alerts
|

Hydrated Hydroxide Complex Dominates the AIE Properties of Nonconjugated Polymeric Luminophores

Abstract: Nontraditional intrinsic luminescence (NTIL) which always accompanied with aggregation‐induced emission (AIE) features has received considerable attention due to their importance in the understanding of basic luminescence principle and potential practical applications. However, the rational modulation of the NTIL of nonconventional luminophores remains difficult, on account of the limited understanding of emission mechanisms. Herein, the emission color of nonconjugated poly(methyl vinyl ether‐alt‐maleic anhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 53 publications
6
24
0
Order By: Relevance
“…Recently, with the help of steady and transient absorption and emission spectrum, we unambiguously confirmed that SWs adsorbed or confined at nanoscale interface in the form of OH -•H 2 O could emit bright colors as non-conjugation luminophors [36][37][38][39] , which answers a century of debate on that water is colored or colorless liquid 40,41 . Differing from the traditional hydrogen bonding of water, the hydroxyl (hydroxide) groups and water molecules in structural water are mainly combined through the spatial interaction between the p orbitals of O atoms, which is a new kind of weak interaction with the characteristics of conjugated π bond and transient feature (Scheme 1c).…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…Recently, with the help of steady and transient absorption and emission spectrum, we unambiguously confirmed that SWs adsorbed or confined at nanoscale interface in the form of OH -•H 2 O could emit bright colors as non-conjugation luminophors [36][37][38][39] , which answers a century of debate on that water is colored or colorless liquid 40,41 . Differing from the traditional hydrogen bonding of water, the hydroxyl (hydroxide) groups and water molecules in structural water are mainly combined through the spatial interaction between the p orbitals of O atoms, which is a new kind of weak interaction with the characteristics of conjugated π bond and transient feature (Scheme 1c).…”
Section: Introductionsupporting
confidence: 53%
“…Fluorescence spectra of different AMOH (AM + = Li + , Na + , K + , Rb + , Cs + ) solution with DMSO as solvent (a) and at varied concentration of KOH (b); Time-resolved luminescence decay profiles of KOH (c) and LiOH solution (d).Excitation and emission spectrum of varied alkali metal hydroxide DMSO solution verified the above assumption that Li + could form more stable SWs for photoluminescence emission due to its stronger hydration ability, which could provide additional reaction channels for surface electron and proton transfer (Scheme 1c). As we earlier reported[36][37][38][39] , in fact the PL emission of SWs was independent on the type of adsorbed metal, herein the alkali metal cations, and that, all the AMOH solution with DMSO as solvent showed a very broad emission peak centered at ca. 450 nm with a shoulder at ca.…”
supporting
confidence: 56%
See 3 more Smart Citations